Factors Influencing Good Agricultural Practices (GAP) Implementation among Potato Farmers in Garut Regency, Indonesia - Nabila An Nadjib; Anna Fatchiya; Dwi Sadono (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study aimed to analyze the level of implementation of GAP innovations and the factors that influence it among potato farmers in Garut Regency, West Java, Indonesia. The study used a quantitative approach with an explanatory research design. A total of 125 potato farmers were selected through proportionate stratified random sampling from five potato production center districts in Garut Regency. Data were collected through surveys, observations, and in-depth interviews, then analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results showed that the overall level of GAP implementation was high, but the components of certified seed use, soil management, balanced fertilization, and integrated pest management were still low. PLS-SEM results confirmed that farmer characteristics, perceptions of innovation characteristics, extension approaches, and cooperative support had a positive and significant influence on GAP implementation, with perceptions of innovation characteristics being the most dominant factor. Based on these findings, it is necessary to strengthen farmers' capacity by increasing access to information, improving the quality of more participatory extension approaches, and optimizing the role of cooperatives to expand farmers' access to information, financing, and markets to support the implementation of GAP more effectively and sustainably.